Πλάτωνος Κήποι - Γκολέμη, Χρυσή (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αρχιτεκτόνων Μηχανικών. Τομέας Αρχιτεκτονικής Γλώσσας, Επικοινωνίας και Σχεδιασμού, 2014)
“Plato’s Gardens” is a self-managed urban garden in the area of Akadimia Platonos, in the center of Athens. It is the project of creating a model park of urban agriculture, based on Permaculture principles. Permaculture is an integrated design system of holistic thinking, which aims to create socially, economically and ecologically sustainable communities. In this time of crisis, “Plato’s Gardens” is designed to be a sustainability center, based on small-scale collective agriculture in the urban environment. The project takes place in an area of 20 acres, including a building of 800sq.m. total coverage which is being reused. It comprises the cultivation of a plurality of species of the Attic landscape, including vegetables, vines, citrus, olive, almond and chestnut trees. Furthermore, it provides functions for storage, outdoor market for the disposal of goods, small-scale winery, dining and recreation, administration, multipurpose hall, as well as squares and promenades. Finally, it includes a model unit of aquaponic production, with main character that of education and research. Aquaponics is an innovative method of growing organic vegetables and fish, in a symbiotic environment. Water from the fish tank is fed to a hydroponic system, wherein the fish waste is absorbed by plants as a fertilizer and the clean water is then recirculated back to the fish. In summary, this effort aims to provide the people in a big city the potential for self-organization and self-sufficiency, based on the shift in the primary production sector, while taking care of the land and the city.